Accessibility measurement of China's coastal ports from a land-sea coordination perspective - An empirical study. (December 2022) - Guo, Jianke; Wang, Ziqi; Yu, Xuhui
Abstract: Port accessibility is a key indicator for assessing the location advantage of coastal ports, which can concentratedly reflect the core competitiveness of ports, including the connectivity with hinterland and foreland, as well as the facilitation of land-sea intermodal transport. Therefore, scientific evaluation of port accessibility and precise identification of its internal structure is of great significance for implementing effective measures to enhance port competitiveness. In view of the lack of studies on port accessibility modeling considering land-sea combination, this paper aims to establish a port accessibility analysis framework that can compare hinterland and foreland advantages from the perspective of land-sea coordination. This study used railway freight rate big data for the first time to compare the foreland and hinterland accessibility to ports in a unified analysis and measurement framework based on complex network theory. Using China's coastal ports as a case study, the comprehensive measurement of port accessibility from the perspective of land-sea coordination is presented. The research results show that the proposed accessibility model depicts the essential port accessibility characteristics dominated by freight. The model can also illustrate the advantages and disadvantages of both the foreland and hinterland accessibility of different ports. Furthermore, it can reveal what land and sea strategies are appropriate for regionally competitive ports of different location types and provide a decision-making reference for port authorities. Highlights: We propose that the current research on port accessibility is in the comprehensive distance stage. A port hinterland accessibility model is established based on railway freight rate big data and complex network theory. A new perspective for the combination modeling of port hinterland and foreland accessibility is provided. China's coastal ports are first taken as example to analyze land and sea location advantages.